Enclosure masonry wall systems worldwide : typical masonry wall enclosures in Belgium, Brazil, China, France, Germany, Greece, India, Italy, Nordic Countries, Poland, Portugal, The Netherlands and U.S.A. /: typical masonry wall enclosures in Belgium, Brazil, China, France, Germany, Greece, India, Italy, Nordic Countries, Poland, Portugal, The Netherlands and U.S.A. (2014) - Unknown
No abstract available